Dancing in Early Productions of The Beggar's Opera. (November 2015) - Barlow, Jeremy; Goff, Moira
Abstract : John Gay's The Beggar's Opera was accepted for production by John Rich, manager at the Theatre Royal, Lincoln's Inn Fields, and received its premiere in January 1728. With its twin satirical targets of Italian opera and political corruption, and its fresh approach to musical entertainment, the opera had an unprecedented success during its first season and continued to be performed every year in London for the remainder of the century. Alongside the many songs, the libretto indicates three contrasting ensemble dances, introduced at key moments of the drama. These dances have been overlooked in most studies of The Beggar's Opera. The article investigates the significance of the dances within the ballad opera, the dancers who may have performed them and what they may have been dancing. Each dance and its music is analysed in detail, and placed within the context of the dance repertoire and wider theatrical background at Lincoln's Inn Fields. The authors also demonstrate the importance of dance in attracting audiences at Lincoln's Inn Fields; and show how, as box office receipts for The Beggar's Opera eventually declined, Rich stimulated demand by introducing divertissements and entr'acte dances unrelated to the show.